IMMUNOMODULATING THERAPY OF INFLUENZA AND ACUTE RESPIRATORY INFECTIONS IN HOSPITALS CHILDREN - E.A. Dondurey; L.V. Osidak; V.F. Sukhovetskaya; E.G. Golovachyova; V.V. Zarubayev; V.P. Drinevskiy; L.N. Gladchenko (Вопросы современной педиатрии, 2010)
It is nesessary to develop medications without antiviral drugs’ shortcomings for the purpose of perfection of acute respiratory infections’ (ARI) treatment. The article describes the results of double-blinded placebo-controlled randomized clinical trial studying effectiveness and safety of sodium desoxyribonucleate (Derinat). The trial included 100 children 0–17 years old with influenza or other ARIs treated in hospitals. The medicine favored to the shorteness of duration of illness owing to more rapid elimination of symptoms of intoxication, fever and catar inflammation in nasopharynx. The level of secretory IgA was increased according to the analysis of nasal washouts, the systems of lipid peroxidation and antioxidant defence were normalized, and also an induction of interferone synthesis and an activation of neutrophils bactericidal action was showed. Authors evaluated economical advantages and safety of the drug. Key words: children, influenza, acute respiratory infections, sodium desoxyribonucleate, treatment, pharmacoeconomical analysis. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(2):45-53)